Magnetic Tactile Display for Heartbeat Emulation - Reuben Louis Idris; Linda Wijayanti; Melisa Mylyadi; Sandra Octaviani (Jurnal Elektro, 2025)
Recently, humanoid robots have developed rapidly and have the potential to become a medical innovation, enhancing human interaction. The ability to realistically mimic a heartbeat is a key feature under development. This research aims to design a ferrofluid-based magnetic tactile display to represent a heartbeat in a humanoid robot. This system utilizes an electromagnetic matrix, ferrofluid, and an Arduino Uno as a magnetic flield controller. Electrocardiogram (ECG) data is used to represent various heart rate patterns, such as normal, bradycardia, and tachycardia. The development results indicate that the magnetic tactile display is capable of providing tactile feedback that corresponds to the heart rate pattern. This device mimics heartbeats based on ECG data by controlling ferrofluid through magnetic field settings, allowing users to feel it tactilely. Testing using an accelerometer sensor shows that the system can replicate normal heartbeats and bradycardia with a small average time difference of 4.52% and 3.93%, respectively. However, in tachycardia, there were difficulties in handling rapid interval changes, resulting in a time error of 31.67%. The results of this study indicate that magnetic tactile displays have great potential in physiological emulation in humanoid robots.